Vertical Gradients of Hono, Nox and o3 in Santiago de Chile - Lissi-Gervaso, E; Rubio-Campos, M (2011)
Gradients of HONO, NOx (NO + NO2) and O3 were measured during an early summer campaign on a high-rise building in downtown Santiago de Chile. Distinct gradients of decreasing concentrations with altitude were observed for HONO and NOx, while O3 concentrations were found to increase with altitude. From the observed daytime maximum of the HONO/NOx ratio the existence of a strong daytime source of HONO is proposed, thus confirming recent results from another measurement site in downtown Santiago, where a high contribution of HONO to the OH radical initiation sources of >50% was observed. Since the HONO/NOx ratio and its daytime maximum were found to be independent of the altitude, it is concluded that HONO is an important OH radical source in Santiago not only close to the ground surface, but also at higher altitudes of the boundary layer. © 2011 Elsevier Ltd.